ANALYSIS OF ETHNO-BASED VALUATION INSTRUMENTS MEASURING HIGHER-ORDER THINKING SKILLS USING ITEM RESPONSE THEORY - Adinata, Yuda candri; Budiyono, Budiyono; Indriati, Diari (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study aims to analyze the appropriateness of ethno-based assessment instruments that can measure Higher Order Thinking Skills based on item response theory. Analysis of the assessment instruments that have been developed have the characteristics of local wisdom and was trialed in three Karanganyar Regency High Schools. Student data analyzed were 288 test scores, consisting of 11th-grade students who had obtained Mathematical Induction material. The method used to explain the results of the analysis uses descriptive analysis. The prerequisite test uses the Unidimensional test for the 35 items that were tested, which means that of the 11 factors formed there is only one dominant factor. The results of the analysis of the three-parameter methods on item response theory for the Goodness of Fit (GoF) parameter model that most fit is the 2-PL model. The results of the analysis can be seen in the output threshold of phase 2 of the 2-PL model regarding the level of difficulty of the grains at values of -0.54 to 2.21. The different grain power index can be seen from the output of the BILOG-MG phase 2 program, which is the slope value in the range of 0.156 to 1.174. Therefore, 34 valid items were obtained with good difficulty and different power levels. Reliability for 34 items 0.71, which means a reliable instrument. It is recommended to conduct a construct validity analysis using confirmatory factor analysis.